4CPS-079 Factors implicated in lipid profile control among hiv-infected patients in treatment with protease inhibitors. (2nd March 2018) - Carballo, N; Ferrández, O; Monge, I; Sala, X Fernandez; Pellicer, R; Berzosa, M; Martinez-Casanova, J; Barcelo-Vidal, J; Knobel, H; Luque, S
Abstract : Background: HIV-infected patients have a higher cardiovascular risk (CVR) than the general population. However, there are not specific preventive interventions for lifestyle modification for this population group. In addition, those treated with protease inhibitors (PIs) may also present dyslipidaemia and require a lipid-lowering-therapy with statins. Purpose: To evaluate which factors linked to cardiovascular disease are independently associated with achieving target lipid levels (TLL) (low-density lipoprotein cholesterol <80 mg/ml). As a secondary objective, to compare the results of cardiovascular disease risk evaluation using two different CVR equations. Material and methods: Prospective observational study performed in a tertiary university hospital from January to September 2017. Inclusion criteria: HIV-patients over 40 years' old treated with PIs (atazanavir/darunavir) and for those taking statins, with a prior time of treatment of at least 6 months. Data collected: demographic, CVR factors (diet, exercise, alcohol, stress, smoking, diabetes, hypertension), clinical data (blood pressure, lipid profile, CD4 count, % patients with undetectable viral load (CV-IDL), treatment (PIs, statins, other lipid-lowering-drugs (LLD), and potential drug-interactions (DI)). Statistics: categorical variables, n(%); quantitative variables, mean ±SD. Patients with and without TLL were compared. A binary logistic regression to identify factors independently associated with achieving TLL was used. For RCV calculation, the REGICOR and the calculator of the American Society of Cardiology (ASCVD) were used. Results: One hundred and twenty-one patients included: 99 (81.8%) with darunavir and 22 (18.2%) atazanavir. Age: 53.2 (9.2) years; 91% (75.2) males. Clinical data: cholesterol (mg/dl): total: 188.7 (40.0), LDL-cholesterol:119. 0 (32.1), HDL-cholesterol: 47.1 (14.9); triglycerides: 159.0 (105.2); CD4 (cells/µL): 722.6 (350.4);% CV-IDL: 104 (86). Treatment data: statins: 32 (26.4); other LLD: 9 (7.4); potential DI: 32 (26.4); severe DI: 3 (2.5). Multivariate analysis: factors independently associated with LTT: diet adherence (OR 2.398 (95% CI: 1038 to 5.541); p=0.038). Patients classified with high CVR: REGICOR: 7 (5.8%) and ASCVD: 59 (48.8%). Conclusion: Adherence to diet was the only factor associated with the achievement of the target lipid levels, which highlights the need to carry out diet education within pharmaceutical care. A discrepancy in the estimation of CVR between the different scales was observed. The ASCVD scale classified a greater percentage of patients as having high CVR than the REGICOR. No conflict of interest